2023
DOI: 10.3390/metabo13060712
|View full text |Cite
|
Sign up to set email alerts
|

Free Radicals and Obesity-Related Chronic Inflammation Contrasted by Antioxidants: A New Perspective in Coronary Artery Disease

Abstract: We are surrounded by factors called free radicals (FR), which attach to the molecules our body is made of, first among them the endothelium. Even though FR are to a certain extent a normal factor, nowadays we face an escalating increase in these biologically aggressive molecules. The escalating formation of FR is linked to the increased usage of man-made chemicals for personal care (toothpaste, shampoo, bubble bath, etc.), domestic laundry and dish-washer detergents, and also an ever wider usage of drugs (both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 198 publications
0
6
0
Order By: Relevance
“…The results showed that aloe vera gel provided better results than CHX [ 80 ]. These studies have highlighted the mechanisms of action of aloe vera which has the following: Anti-inflammatory properties thanks to the content of acemannans and anthraquinones which can reduce inflammation by acting on inflammatory processes at a cellular level [ 103 ]; Antioxidant properties thanks to the presence of vitamins C and E and flavonoids which protect cells from damage caused by free radicals [ 51 , 104 ]; Antimicrobial action preventing infections and helping to maintain oral hygiene [ 80 , 105 ]; Effects on bacterial plaque, influencing its growth and formation [ 106 ]; Effects on the immune system by helping to regulate the immune response and reduce inflammation [ 107 ]; Positive effects on wound healing by stimulating collagen production especially in the presence of small wounds or irritations caused by orthodontic devices [ 108 , 109 ]; Hydrating and soothing effects on skin and oral mucous membranes, improving patient comfort and reducing irritation [ 110 , 111 ]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results showed that aloe vera gel provided better results than CHX [ 80 ]. These studies have highlighted the mechanisms of action of aloe vera which has the following: Anti-inflammatory properties thanks to the content of acemannans and anthraquinones which can reduce inflammation by acting on inflammatory processes at a cellular level [ 103 ]; Antioxidant properties thanks to the presence of vitamins C and E and flavonoids which protect cells from damage caused by free radicals [ 51 , 104 ]; Antimicrobial action preventing infections and helping to maintain oral hygiene [ 80 , 105 ]; Effects on bacterial plaque, influencing its growth and formation [ 106 ]; Effects on the immune system by helping to regulate the immune response and reduce inflammation [ 107 ]; Positive effects on wound healing by stimulating collagen production especially in the presence of small wounds or irritations caused by orthodontic devices [ 108 , 109 ]; Hydrating and soothing effects on skin and oral mucous membranes, improving patient comfort and reducing irritation [ 110 , 111 ]. …”
Section: Discussionmentioning
confidence: 99%
“…Antioxidant properties thanks to the presence of vitamins C and E and flavonoids which protect cells from damage caused by free radicals [ 51 , 104 ];…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it is vital to examine how food processing might affect antioxidant content by researching prescribed concentrations of individual antioxidants or specific combinations that demonstrate a higher capacity to reduce oxidative stress in individuals with obesity. Moreover, exploring the potential advantages of novel antioxidants might offer fresh perspectives on their influence on obesity [114,115]. Thus, addressing these research gaps will facilitate a more comprehensive understanding of the mechanisms underlying the effects of dietary antioxidants on obesity.…”
Section: Challenges and Future Directions In Researchmentioning
confidence: 99%
“…It is one of the leading causes of mortality and morbidity in the Western world. Thus, cardiovascular diseases such as heart attack, peripheral arterial disease, and others are the clinical manifestations of atherosclerosis [ 6 ]. Dyslipidaemia, diabetes mellitus, arterial hypertension, smoking, psychosocial factors, obesity, limited physical activity, and family history are the main risk factors for atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%